If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -18 + -8x = -10(x + 4) Reorder the terms: -18 + -8x = -10(4 + x) -18 + -8x = (4 * -10 + x * -10) -18 + -8x = (-40 + -10x) Solving -18 + -8x = -40 + -10x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '10x' to each side of the equation. -18 + -8x + 10x = -40 + -10x + 10x Combine like terms: -8x + 10x = 2x -18 + 2x = -40 + -10x + 10x Combine like terms: -10x + 10x = 0 -18 + 2x = -40 + 0 -18 + 2x = -40 Add '18' to each side of the equation. -18 + 18 + 2x = -40 + 18 Combine like terms: -18 + 18 = 0 0 + 2x = -40 + 18 2x = -40 + 18 Combine like terms: -40 + 18 = -22 2x = -22 Divide each side by '2'. x = -11 Simplifying x = -11
| f(x)=15x^4+8x^3-18x^2+1 | | m-1=-13+3m | | 3/103/4 | | 3(2x-5)+24-4x=9 | | 25x^2=-45x-18 | | 2/3(x-9)^-(1/3) | | -10-3a=a-6-3a | | x+x+55(x+38)=180 | | 25x^2+45x-18=0 | | 45=9-2b | | 4-4a=-3a+a | | 3k-2=4 | | .25x+3=-9 | | x=4x-0.1x^2 | | 11ln(9x)=12 | | 7+8r=7-4r | | x+x+43*x-32=180 | | 3(a-10)=42 | | -.5x+15=20 | | -2+5x=-3x+7x | | p+.12p=56 | | -5=a^2+3 | | t/3+t/2-350=270 | | 1-4v=15-6v | | 11+x=-33 | | http://media.apexlearning.com/Images/201305/30/25030d05-eb1d-46a7-bf10-8e6086df63c3.gif | | -12/6=X | | p+.12p=52 | | 5n+4n=8n-7 | | 4x+3y-4=7y+12 | | 4x+2x=13 | | 3a+2(a+6)=52 |